"Tyran prosi o rękę najładniejszej z niewiast polskich": obraz małżeństwa Joanny Grudzińskiej i Wielkiego Księcia Konstantego w świetle pamiętników = - Wesołowska, Aleksandra (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Konstantin Pavlovich Romanow, a brother of mighty Russian tsars Alexander I and Nicholas I, the commander-in-chief and de facto the viceroy of the Congress Poland. The Duke became famous mostly as an oppressor of the Poles, a raving madman and belvedere animal. However, source research shows a lot of changes in his behavior. Among the citizens of Warsaw, the capital of Poland, there could be found some who spoke dearly about the Duke?s humor, caregiving and even a kind of fondness of the Polish people. Joanna Grudzińska, who agreed to marry the tyrant, is considered to be the main reason of these transformations. It is worth to devote a moment to take a look at this marriage and what the citizens of Warsaw thought of it.
Keywords: Romanow, Konstanty Pawłowicz (wielki książę rosyjski; 1779-1831); Grudzińska, Joanna (1795-1831); pamiętnik